Development of a lean principles framework for ERP implementation process - Alturkistani, Adnan Qurban A. (Cranfield University, 2018)
The aim of this research is to develop a novel framework based on lean principles and tools to be exploited in managing ERP implementation processes in order to enhance the overall success rate of the implementation project, which in turn minimises cost and time overruns. The framework consists of three stages built in a logical sequence taking into consideration the requirements of ERP projects implementations and the lean transformation principles. The first stage starts with an assessment model to measure the organisational readiness for implementing ERP system using leanness assessment approach. The second stage of the framework introduces the use of the Obeya lean tool along with a change management model to help visualize and streamlining the process of ERP implementation. In the final stage, a value stream mapping technique is used to identify potential waste occurrence and eliminate non-value adding activities from the process. As a result, a new eight stages ERP implementation process is developed and presented with descriptions on the activities encompassed in each stage. A research methodology consisting of four major phases was employed to attain the targeted objectives of the research; beginning with project initiation and contextual definition followed by data collection and field study. The data acquired from the previous two phases were used to conduct a thorough analysis from which key findings were drawn and used in the creative development of the readiness assessment model and the framework. Finally, elementary aspects of the framework were put to scrutiny through live case studies and professional expert judgement. The author made use of both qualitative and quantitative research measures. A validation for the ERP readiness assessment model is conducted initially on three case studies, and then the whole framework is validated through two other case studies and experts’ judgments. The results and overall feedback reflected a high level of acceptance of the framework structure and approach. The novel framework has the capability to improve the ERP implementation process providing it is utilised fully. It helps organisation to successfully deliver ERP systems on time, on budget, and with the required functionalities with high-level of acceptance from all stakeholders.
Keywords: ERP implementation; ERP readiness; lean; lean IT; leanness assessment